Decolonizing Parenting Typologies: Bedengah and Mentanak as Cultural and Religious Systems among Sasak Muslim Families - Zulkarnain Zulkarnain; Abdul Muhid; Moch. Choirul Arif; Auwalu Shuaibu Muhammad; Ishom Fuadi Fikri (Universitas Islam Negeri Madura, 2026)
This study examines Bedengah and Mentanak — traditional parenting systems practiced by Sasak Muslims in Lombok, Indonesia — proposing them as culturally-regulated and religiously-regulated frameworks that extend beyond Western developmental typologies. Through ethnographic research conducted across three traditional villages over nine months, involving 30 informants and utilizing participant observation, in-depth interviews, and documentation analysis, the study reveals how these parenting systems incorporate age-specific practices, ritual ceremonies, intergenerational skill transmission, and extended family involvement deeply rooted in Sasak cultural values and Islamic teachings. The findings expose three critical dimensions inadequately captured in Baumrind's (1971) conventional framework: (1) cultural tradition as a self-sustaining regulatory system governing child behavior across developmental stages; (2) religion as a structural architecture rather than mere value content shaping parenting; and (3) parenting as a collective community responsibility extending far beyond the parent-child dyad. While Bedengah and Mentanak provide robust cultural identity formation and moral scaffolding, they also confront contemporary pressures stemming from higher educational aspirations among youth, debates over Islamic orthodoxy regarding local ritual legitimacy, and household economic constraints. This study contributes theoretically to cross-cultural parenting scholarship by proposing an indigenous conceptual framework that recognizes cultural and religious structure — not merely content — as the organizing logic of child-rearing, with direct implications for designing culturally adaptive child-protection policies, family-welfare programs, and parenting education curricula in rural Muslim-majority communities in Indonesia.